Determinants of access and utilization of cervical cancer treatment and palliative care services in Harare, Zimbabwe - O. Tapera; G. Dreyer; W. Kadzatsa; A. M. Nyakabau; B. Stray-Pedersen; S. J. H. Hendricks (BMC, 2019)
Abstract Background Cervical cancer treatment and care services have remained largely centralized in Zimbabwe thereby entrenching inequities to access amongst patients. The objective of this study was to investigate the determinants of access to treatment and care among women with cervical cancer in Harare, Zimbabwe. Methods A sequential explanatory mixed methods design was used. In phase 1, three surveys (namely community, patient and health worker) were conducted with sample sizes of 143, 134 and 78 participants respectively. Validated structured questionnaires programmed in Android tablet with SurveytoGo software were used for data collection during the surveys. Univariate, bivariate and multivariate logistic regression analyzes were conducted using STATA® version 14 to generate descriptive statistics and identify determinants of access to cervical cancer treatment and care. In phase 2, 16 in-depth interviews, 20 key informant interviews and 6 focus groups were conducted to explain quantitative data. Participants were purposively selected and saturation principle was used to guide sample sizes. Manually generated thematic codes were processed in Dedoose software to produce final outputs for qualitative study. Results Knowledge of causes (p = 0.046), perceptions of adequacy of specialists (p < 0.001), locus of control (p = 0.009), service satisfaction (p = 0.022) and walking as a means of reaching nearest health facilities (p < 0.001) were associated with treatment or perceptions of access by healthy women. Perceptions of access to treatment amongst health workers were associated with their basic training institution (p = 0.046), health service quality perceptions (p = 0.035) and electricity supply status in their respective health facilities (p = 0.036).Qualitative findings revealed health system, societal and individual factors as barriers to accessing treatment and palliative care. Conclusions There are numerous prevailing multi-dimensional barriers to accessing cervical cancer treatment and palliative care in a low -income setting. The findings of this study revealed that heath system and societal factors were more important than individual level factors. Multi-sectoral approaches are recommended to address all the multifaceted barriers in order to improve cervical cancer treatment and palliative care access for better outcomes in resource-limited contexts.